Ecosystem and Biodiversity of Amazonia - Juhani Mikkola, Heimo (IntechOpen, 2021)
The Amazonia is the largest continuous river basin and rainforest ecosystem in the world. In all aspects it is a natural wonder, and the rainforest with its billions of trees is a vital carbon store that slows down the advance of global warming. It is home to one million indigenous people and some three million species of plants and animals. There have been many climate fluctuations during the last 55 million years of its existence, but never before have "the lungs of the world" been at greater risk than they are today due to uncontrolled fires, expanding agriculture and heavy industrial development in the forms of oil drilling, mining and large hydroelectric dams. Over twelve chapters, this book describes the anthropological, biological and industrial problems facing the Amazonia, and seeks to find new solutions.